Hexagon Fraud Analysis dn Detecting Financial Fraudulent Statements on Manufacturing Companies in Indonesia - Gusdinda Ramadhanti Putri; Erni Suryandari Fathamaningrum (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the fraud hexagon model through the influence of Pressure, Capability, Opportunity, Rationalization, Arrogance, and Collusion on financial statement fraud in Indonesia. This study uses a logistic regression model using purposive sampling with data criteria for companies that have been listed on the Indonesia Stock Exchange (IDX) from 2019 to 2020, and the manufacturing company has complete data related to the variables needed during the research period from 2019 to 2020. The results showed that asset growth, ROA, changes in directors of manufacturing companies, and collution in Indonesia have a positive relationship with the incidence of manufacturing companies committing fraud. While other variables (LEV, DDout, Receivable, BKG, CPA, and COL) have no influence on the incidence of manufacturing companies committing fraud.